catena-Poly[[diaquacopper(II)]-μ-hydroxido-κ(2) O:O-μ-[4-(4H-1,2,4-triazol-4-yl)benzoato]-κ(2) N (1):N (2)] - Shi, Haochen (International Union of Crystallography, 2011)
The title compound, [Cu(C(9)H(6)N(3)O(2))(OH)(H(2)O)(2)](n), adopts a chain motif along [010] in which the Cu(II) atoms are bridged by hydroxy groups and 4-(1,2,4-triazol-4-yl)benzoate (tab) ligands. The Cu(II) atom lies on an inversion center and is six-coordinated by two N atoms from two tab ligands, two hydroxy groups and two water molecules, giving a distorted octahedral geometry. The hydroxy group and the tab ligand are located on a mirror plane. One of the water H atoms is disordered over two positions with equal occupancy factors. Intermolecular O—H⋯O hydrogen bonds extend the chains into a layer parallel to (100) and C—H⋯O hydrogen bonds connect the layers into a three-dimensional network.